Cache performance of chronological garbage collection - Ding, Yuping (My University, 1999)
This thesis presents cache performance analysis of the Chronological Garbage Collection Algorithm used in LVM system. LVM is a new Logic Virtual Machine for Prolog. It adopts one stack policy for all dynamic memory requirements and cooperates with an efficient garbage collection algorithm, the Chronological Garbage Collection, to recycle space, not as a deliberate garbage collection operation, but as a natural activity of the LVM engine to gather useful objects. This algorithm combines the advantages of the traditional copying, mark-compact, generational, and incremental garbage collection schemes. In order to determine the improvement of cache performance under our garbage- collection algorithm, we developed a simulator to do trace-driven cache simulation. Direct-mapped cache and set-associative cache with different cache sizes, write policies, block sizes and set associativities are simulated and measured. A comparison of LVM and SICStus 3.1 for the same benchmarks was performed. From the simulation results, we found important factors influencing the performance of the CGC algorithm. Meanwhile, the results from the cache simulator fully support the experimental results gathered from the LVM system: the cost of CGC Is almost paid by the improved cache performance. Further, we found that the memory reference patterns of our benchmarks share the same properties: most writes are for allocation and most reads are to recently written objects. In addition, the results also showed that the write-miss policy can have a dramatic effect on the cache performance of the benchmarks and a write-validate policy gives the best performance. The comparison shows that when the input size of benchmarks is small, SICStus is about 3-8 times faster than LVM. This is an acceptable range of performance ratio for comparing a binary-code engine against a byte-code emulator. When we increase the input sizes, some benchmarks maintain this performance ratio, whereas others greatly narrow the performance gap and at certain breakthrough points perform better than their counterparts under SICStus.
Keywords: Garbage collection (Computer Science)